2022
DOI: 10.1128/spectrum.00916-22
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Phasevarions Control Multiple Virulence Traits, Including Vaccine Candidate Expression

Abstract: S. pneumoniae is the world’s foremost bacterial pathogen. S. pneumoniae encodes a phasevarion (phase-variable regulon), that results in differential expression of multiple genes. Previous work demonstrated that the pneumococcal SpnIII phasevarion switches between six different expression states, generating six unique phenotypic variants in a pneumococcal population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
0
13
1
Order By: Relevance
“…Analysis of these TRD sequences revealed that there are four unique 5 ′ -TRD sequences, and four unique 3 ′ -TRD sequences present in these strains (Figure 3B ; full sequences and analysis in Supplementary Data 1 ), meaning a potential 16 unique HsdS proteins are possible dependent on the encoded TRDs present (four possible 5 ′ -TRD x four possible 3 ′ -TRD). This is unlike other phase-variable Type I systems, such as the SpnD39III system in S. pneumoniae ( 34 , 37 , 38 , 61 ), and the phase-variable Type I system in S. suis , ( 39 ) where all strains encode the same TRDs, and therefore shuffle between the same complement of expressed HsdS proteins. Our prototype strains of AP76 and JL03 encoded a subset of these sixteen potential TRDs: AP76 encoded a combination of 5’-TRD-1 and 3’-TRD-1 (abbreviated TRD1-1) and TRDs 1-2, 2-2 and 2-1 (comprising alleles A-D; Figure 3C ); while in strain JL03 we found TRDs 2-1, 2-3, 3-3 and 3-1 (comprising alleles D-G; Figure 3D ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Analysis of these TRD sequences revealed that there are four unique 5 ′ -TRD sequences, and four unique 3 ′ -TRD sequences present in these strains (Figure 3B ; full sequences and analysis in Supplementary Data 1 ), meaning a potential 16 unique HsdS proteins are possible dependent on the encoded TRDs present (four possible 5 ′ -TRD x four possible 3 ′ -TRD). This is unlike other phase-variable Type I systems, such as the SpnD39III system in S. pneumoniae ( 34 , 37 , 38 , 61 ), and the phase-variable Type I system in S. suis , ( 39 ) where all strains encode the same TRDs, and therefore shuffle between the same complement of expressed HsdS proteins. Our prototype strains of AP76 and JL03 encoded a subset of these sixteen potential TRDs: AP76 encoded a combination of 5’-TRD-1 and 3’-TRD-1 (abbreviated TRD1-1) and TRDs 1-2, 2-2 and 2-1 (comprising alleles A-D; Figure 3C ); while in strain JL03 we found TRDs 2-1, 2-3, 3-3 and 3-1 (comprising alleles D-G; Figure 3D ).…”
Section: Resultsmentioning
confidence: 90%
“…The SpnD39III system in S. pneumoniae contains multiple variable hsdS loci which contain inverted repeats, and a gene encoding a recombinase ( creX ). Homologous recombination between these multiple variable hsdS genes via these inverted repeats, and catalysed in part by the associated recombinase ( 36 ), results in the expression of six different methyltransferase variants within a population, which control six different phasevarions, resulting in six different phenotypic sub-variants within a pneumococcal population ( 34 , 37 , 38 ). A phase-variable Type I DNA methyltransferase has also been characterised in the related organism Streptococcus suis ( 39 ), with this system switching between four different HsdS variants.…”
Section: Introductionmentioning
confidence: 99%
“…full sequences and analysis in Supplementary Data 1), meaning a potential 16 unique HsdS proteins were possible dependent on the encoded TRDs present (four possible 5′-TRD x four possible 3′-TRD). This is unlike other phase-variable Type I systems, such as the SpnD39III system in S. pneumoniae (34,37,38,61), and the phase-variable Type I system in S. suis, (39) where all strains encode the same TRDs, and therefore shuffle between the same complement of expressed HsdS proteins. Our prototype strains of AP76 and JL03 encoded a subset of these sixteen potential TRDs: AP76 encoded a combination of 5′-TRD-1 and 3′-TRD-1; 5′-TRD-1 and 3′-TRD-2; 5′-TRD-2 and 3′-TRD-2; 5′-TRD-2 and 3′-TRD-1, which we have named alleles A-D, respectively (Figure 3C).…”
Section: Distribution Of the Phase-variable Methyltransferases In A P...mentioning
confidence: 91%
“…This diversity inherently serves as a bet-hedging strategy in the face of multiple potential invading bacteriophage strains, forbidding any one bacteriophage from eliminating the entire bacterial population ( 6 , 20 ). These variants were also observed to differ in opacity ( 10 ), virulence in mice ( 10 ), as well as human cell infection efficiency and survival in human blood ( 11 ), presumably resulting from Type I RM phase variants inducing differential methylation of host DNA ( 20 ). Other interesting phase variation systems include a programmed inversion targeting the pilV gene (shufflon), leading to phase variants differing in the specificity of their conjugative pili ( 21 ), and a programmed inversion targeting phage tail genes, conferring different host specificity ( 22 ).…”
Section: Introductionmentioning
confidence: 99%